A Methodological Proposal to Evaluate the Sinergical Industry Concentration - Juan Ignacio Dalmau-Porta; Maria del Val Segarra-O\~na (European Regional Science Association (ERSA), 2003)
This study deals with the firms' competitiveness in traditional industries. We understand traditional industry as the one that has transmitted its knowledge generation after generation, and it also has some specific characteristics, such as not being a new industry because its activities have been carried out for many years, to have small and medium sized businesses with little or no presence of transnational firms or having little investment on technology and activities of research and development. The objective of this paper is to present a methodological process for the study and evaluation of the impact of the sinérgic geographical concentration of an industry in its competitiveness. The geographical concentration is a factor of great importance, facilitates the exchange and the cooperation among research centers, among the clients and the suppliers of the region, and it promotes research in the industry (Porter, 1998). On the other hand, the specific concentration of activities in a concrete zone attracts the specialized knowledge. The importance of the geographical concentration and the evidence of the existence of industrial clusters has been studied in an extensive manner through time; Saxenian (1996) analyzed the organization and the characteristics of the electronic firms of Sillicon Valley, Glasmeier (1991) the Swiss clocks, Faulkner and Anderson (1987) the film industry in Hollywood, Scott (1991) the electronic-aeroespacial industry in the south of California, and Abrupt (1982) studied the organization of firms in the north of Italy. Following Kaplan (1986), it turns out to be difficult to imagine that theories in the field of management can be verified, if the test is not carried out inside its context. These tests should serve not only to describe the existence or not of procedures, but also to deduce and to contrast how and why certain practices have to be carried out. If the intention of the researcher is to generate a theory, taking into account the theoretical framework and the key questions to answer are how they are created and how they influence the geographical concentration in the competitiveness of an industry, the most appropiate would be to carry out an explanatory type case study. Some cases will be studied according to Rouse and Daellenbach, (1999). The study of cases to be carried out follows the model proposed by Pérez (1998). The method that will be used in this study, interviews in depth, is classified as direct obtaining of data. The type of interview used is the so call interview of open answers (King, 1994). This technique combines the advantages of the use of closed questionnaires along the qualitative interviews. In the paper, we present an instrument to evaluate the impact of the geographical concentration.
Keywords: 330